Not the Last Piece of the Puzzle: Niphargus Phylogeny in Hungary - Gergely Balázs; Špela Borko; Dorottya Angyal; Valerija Zakšek; Anna Biró; Cene Fišer; Gábor Herczeg (Diversity, 2023)
The Palaearctic genus Niphargus is a promising model system to understand subterranean fauna genesis in Europe. The Pannonian Plain (mainly covered by Hungary) in Central Europe, once being the area of the Paratethys, is a key area for Niphargus diversification. However, our knowledge on Hungarian species of Niphargus is primarily based on sporadic taxonomical works from the pre-molecular era. Here, we studied 14 localities, covering the eight valid Hungarian species of Niphargus and including nine previously unstudied populations. Based on sequences of three gene fragments, we reconstructed their phylogeny using maximum likelihood and Bayesian approaches. We found that not all Hungarian species of Niphargus are closely related, and even species sampled at the same localities can belong to different clades. Some Hungarian species form monophyletic clades, while others are nested in various non-Hungarian lineages. The new populations are all genetically distinct from the known species. Our results suggest that the Hungarian Niphargus fauna has originated from seven unrelated clades and its diversity is underestimated due to unknown populations and cryptic species. The detection of genetically distinct species of Niphargus from non-carbonate regions calls for further research efforts. The high diversity and the number of putative new species in the N. tatrensis clade warrants further, high-resolution phylogenetic studies.